Aldosterone antagonists improve ejection fraction and functional capacity independently of functional class: a meta-analysis of randomised controlled trials. Issue 23 (12th July 2012) - Phelan, Dermot; Thavendiranathan, Paaladinesh; Collier, Patrick; Marwick, Thomas H
Abstract : Context: Current guidelines recommend the use of aldosterone antagonists (AA) in patients with moderately severe to severe symptoms [New York Heart Association (NYHA) class III to IV] and systolic heart failure. Objective: To determine the efficacy of AA in improving ejection fraction (EF) and functional capacity and to assess whether this effect was influenced by baseline NYHA classification. Study design: Meta-analysis of randomized controlled trials. Data extraction performed independently by two researchers. Data Sources: MEDLINE and the Cochrane Library. Study Selection: Prospective randomized controlled trials using AA were included if there was a clear description of the baseline NYHA classification and change in EF in patients from study initiation to completion. Results: Data from 1, 575 patients enrolled in fourteen studies were included. Overall, there was a weighted mean improvement in EF of 3.2% and in NYHA classification of 0.13 in subjects treated with AA when compared to controls (p<0.001). A mixed effects meta-regression analysis revealed that baseline NYHA was not predictive of improvement in EF (p=0.67) nor NYHA status (p=0.18). Conclusions: The results of this meta-analysis suggest that AA is associated with significant improvements in EF and functional class independent of baseline functional capacity. This supports and expands on the recently published EMPHASIS-HF trial and suggests that the current restriction of AA use to patients with NYHA class III-IV symptoms should be reconsidered.